Rules of RNA specificity of hnRNP A1 revealed by global and quantitative analysis of its affinity distribution - Jain, Niyati (Proc Natl Acad Sci U S A, 2017)
Heterogeneous nuclear ribonucleoprotein A1 (hnRNP A1) is a multipurpose RNA-binding protein (RBP) involved in normal and pathological RNA metabolism. Transcriptome-wide mapping and in vitro evolution identify consensus hnRNP A1 binding motifs; however, such data do not reveal how surrounding RNA sequence and structural context modulate affinity. We determined the affinity of hnRNP A1 for all possible sequence variants (n = 16,384) of the HIV exon splicing silencer 3 (ESS3) 7-nt apical loop. Analysis of the affinity distribution identifies the optimal motif 5′-YAG-3′ and shows how its copy number, position in the loop, and loop structure modulate affinity. For a subset of ESS3 variants, we show that specificity is determined by association rate constants and that variants lacking the minimal sequence motif bind competitively with consensus RNA. Thus, the results reveal general rules of specificity of hnRNP A1 and provide a quantitative framework for understanding how it discriminates between alternative competing RNA ligands in vivo.